Psychological features of virtual communication - Nataly Darialova (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2015)
The article is devoted to the study of theoretical analysis of the virtual communication problem. Psychological peculiarities that influence the process of communication in the Internet network are analyzed. The main approaches to the study of virtual communication in the present are presented.